DIFFERENCES BETWEEN MALE AND FEMALE DENTAL ARCH FORM Study in Banjarnese Students of Dentistry Program Medical Faculty of Lambung Mangkurat University (Research Report) - Adhani, Rosihan; widodo, widodo; Muntasir, Adib (Dentino, 2017)
ABSTRACTBackground: Acrylic resin as denture base material has been mostly used. Cleanliness of denture base can be maintained by submerging the denture base into 0,2% chlorhexidine gluconate. Uncleaned denture base can cause Denture Stomatitis.There are the flora accumulation like Candida albicans. Small white gingerhas activity towards Candida albicans. Small white ginger has antifungal role because of its phenol compound. Purpose: This study aims to know the Minimum Inhibitory Concentration value (MIC) of ethanol extract concentration of small white ginger towards Candida albicans growth in submerge of heat cured removable acrylic denture. Method: This experimental study was using post test only with control group design. Acrylic resin was submerged into 30%, 35%, 40%, 45%, 50%, 60%, 70%, 80%, 90%, 100% tratment extract, and as the control group, there are 0,2% chlorhexidine gluconate and 70% ethanol. The data analyzed usedOne Way Anova test and Bonferroni Post Hoc test with 95% confidence level.Result: The result of the study shows thatMIC value of 40%, 45%, 50%, 60%, 70%, 80% 90% and 100% from treatment extract consecutivly are 13.07%; 18.36%; 23.67%; 28.87%; 36.84%; 42.10%; 49.98%; 52.61%. Conclusion: The conclusion of this study is treatment extract can reduce the amount of Candida albicans and 100% treatment extract has better antifungal effect compared to lesser concentrations and 0,2% chlorhexidine gluconate.Keywords: dental arch form, mandibular, gender, Banjarnese